Mr. Putter & Tabby See the Stars - Rylant, Cynthia (New York Harcourt, Inc., 2007)
When Mr. Putter cannot sleep after eating too many of Mrs. Teaberry's pineapple jelly rolls, he and Tabby take a moonlit stroll that ends with the perfect neighborly gathering.
K - 2
Keywords: Cats - Fiction; Neighborliness - Fiction; Night - Fiction